Strategies to Build Education in Mandailing Natal (Steps to Align the Quality of Education Students in Mandailing Natal Regency) - Mukhlis Mukhlis (Budapest International Research and Critics University, 2022)
This study explains that the education sector has a very large role in development in Mandailing Natal Regency. There should be serious efforts to plan quality education in this area. If it is able to improve the level of education, then automatically Mandailing Natal is able to compete in all fields. As one of the drives of the national development is responsible for producing graduates who have deep and broad insights and skills both locally, nationally and internationally and are able to compete with graduates from other schools. So there must be strategies and efforts to improve competitiveness by taking seriously improving the quality of school education. So there must be a strategy to make fundamental changes.